Vaccination coverage of hepatitis B and associated factors among health care workers in Gansu province - Jing An; Na Jin; Jingru Xie; Yuxin Ma; Haixia Liu; Gulipiyan Balajiang; Shuyu Liu; Xiaoshu Zhang (Taylor & Francis Group, 2024)
The investigation was conducted to describe the status of coverage of HBV vaccination among the health care workers in Gansu province and to explore the associated factors of HBV vaccination in this study. A cross-sectional study was conducted among 1544 health care workers from 64 hospitals in Gansu province. A self-designed questionnaire was used to interview the health care workers about HBV vaccination coverage. A multivariate logistic regression model explored the associated factors with HBV vaccination. The vaccination coverage was 89.17% for health care workers, nurses (90.40%) had the highest rate, followed by administration staff (89.38%) and medical technicians (89.30%). The full-dose HBV vaccination coverage was 64.25% for health care workers, and administration staff (65.04%) had the highest rate, followed by nurses (65.00%). This study found that the associated factors with HBV vaccination and full-dose vaccination were the history of training and the detection of serological indicators. The coverage of HBV vaccination among health care workers in Gansu province was high, but full-dose HBV vaccination coverage was low. It is necessary to strengthen the HBV knowledge and training in HBV prevention and treatment among health care workers in Gansu Province.